Editorial: liver stiffness by magnetic resonance elastography and cardiovascular risk in non-alcoholic fatty liver disease-simply associated or more complicated? - YILMAZ, YUSUF (WILEY, 2021)
LINKED CONTENT This article is linked to Park et al papers. To view these articles, visit and
Keywords: FIBROSIS